Peningkatan Literasi Keuangan melalui Pelatihan Pengelolaan Keuangan Berbasis Excel Bagi Siswa SMP Negeri 93 Jakarta - Putri Harynai; Septi Nurmalita; Siti Halizah Salsabilla; Ridho Rambu Bassae (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Financial knowledge remains a challenge for middle school students in Indonesia, particularly those at SMP Negeri 93 Jakarta, where many students come from families with limited access to financial education. This issue is underscored by the national financial literacy rate, which stands at a mere 38,03%, as reported by the Financial Services Authority. In response to this pressing need, this study aimed to evaluate the effectiveness of a practical, technology based financial literacy training workshop for junior high school students. The workshop, conducted over one day, was structured in three key stages included pre-test administered via Google Form to assess baseline knowledge, an interactive training session that emphasized essential concept of financial planning and budgeting practices using excel, and a posttest to measure the improvement in understanding. The results showed a significant enhancement in student’s knowledge and awareness regarding personal finance management. This program demonstrates that a straightforward application-based approach can serve as an effective model for financial literacy education, offering potential for replication in other school through collaboration between universities, schools, and local communities.